Estimating and forecasting European migration: methods, problems and results - Herbert Brücker; Boriss Siliverstovs (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
The specification of macro migration models and, hence, forecasts of migration potentials differ largely in the literature. Two main differences characterise macro migration models: first, whether migration flows or stocks are used as the dependent variable, and, second, whether the heterogeneity in the migration behaviour across countries is considered. This paper addresses both issues empirically using German migration data from 18 European source countries in the period 1967-2001. It finds first that panel unit-root and cointegration tests reject the hypothesis that the variables of the flow model form a cointegrated set, while the hypothesis of cointegration is not rejected for the stock model. The second finding is that standard fixed effects estimators dominate the forecasting performance of both pooled OLS and heterogeneous estimators. Applying the preferred fixed effects estimator, the migration potential from the Central and Eastern European accession countries is estimated at 2.3-2.5 million persons for Germany, which implies a migration potential of 3.8-3.9 million persons for the EU-15. Finally, our estimates indicate that the migration potential in the EU-15 is already exhausted and that the migration potential from Turkey is relatively small.
Keywords: 330; Einwanderung; internationale Wanderung - Prognose; Prognoseverfahren; Prognosemodell; Prognosegenauigkeit; Migrationsforschung; Wanderungspotenzial; Schätzung - Methode; Arbeitskräftemobilität; regionale Mobilität; Europäische Union; Bundesrepublik Deutschland